Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12884-018-2135-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving women’s knowledge about prenatal screening in the era of non-invasive prenatal testing for Down syndrome – development and acceptability of a low literacy decision aid

Abstract: BackgroundAccess to information about prenatal screening is important particularly in light of new techniques such as non-invasive prenatal testing (NIPT). This study aimed to develop and examine the acceptability of a low literacy decision aid (DA) about Down syndrome screening among pregnant women with varying education levels and GPs.MethodsWe developed a DA booklet providing information about first-trimester combined testing, maternal serum screening, and NIPT. GPs and women participated in a telephone int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…Our study is designed to better identify barriers to informed decision-making regarding prenatal testing and in the ongoing second phase, attempt novel education interventions to improve genetic literacy and patients' confidence in their decisions. Participants in our study indicated that a prenatal testing mobile application would help individuals to acquire the most accurate knowledge in a more accessible way, as suggested by other researchers (Choi & Kim, 2014;Smith et al, 2018;Yee et al, 2014). For example, one of the participants discussed the difficulties of finding trustworthy, easy-to-understand information on the Internet.…”
Section: Discussionsupporting
confidence: 52%
“…Our study is designed to better identify barriers to informed decision-making regarding prenatal testing and in the ongoing second phase, attempt novel education interventions to improve genetic literacy and patients' confidence in their decisions. Participants in our study indicated that a prenatal testing mobile application would help individuals to acquire the most accurate knowledge in a more accessible way, as suggested by other researchers (Choi & Kim, 2014;Smith et al, 2018;Yee et al, 2014). For example, one of the participants discussed the difficulties of finding trustworthy, easy-to-understand information on the Internet.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, maternity health care providers should be aware of women's individualized experiences on prenatal ultrasound examinations and provide appropriate education [45,46]. Thus, antenatal childbirth classes should design information to improve women's genetic literacy on prenatal screen procedures [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…As 29 women in our present study sought health information from the Internet compared to 16 women who attended traditional education classes, it is recommended that effective educational strategies should be considered. These strategies may include decisional aids and interactive computerized information aids, which have been proven to enhance genetic health literacy and reduce decisional conflict [47,48,50]. Importantly, antenatal care nurses should acquire up-to-date knowledge of varying prenatal screening tests including advantages, risks, and costs.…”
Section: Increased Education Regarding Common Prenatal Screen Testsmentioning
confidence: 99%
“…30 Decision aids could potentially improve patient knowledge prior to screening and have been used to improve knowledge for other screening programmes. [31][32][33][34] They could be used to explain the diagnostic test, conditions that could be diagnosed, quantitative information relating to diagnostic accuracy and the risks and benefits of treatment. They could also be used to promote clarification of patients' preferences about the screening and potential consequences to improve patient knowledge.…”
Section: Practice and Policy Implicationsmentioning
confidence: 99%